Analisis Determinan Tax Morale Pelaku Usaha Mikro Kecil dan Menengah (UMKM) - Risqi Firda Salsabila; Afifudin Afifudin; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2023)
Tax Morale can motivate someone to pay taxes as a voluntary contribution to the state which can affect taxpayer compliance. The following research aims to determine the effect of trust in the government, awareness of taxpayers, and knowledge of taxation on the Tax Morale of MSME actors. This research is a correlational quantitative research using primary data using purposive sampling technique. The results of this study indicate: 1) Trust in the Government variable has a significant positive effect on the tax morale of MSME actors, 2) Taxpayer Awareness variables have a significant positive effect on the tax morale of MSME actors, 3) Tax Knowledge Variable has no effect on taxes the morale of MSMEs.Keyword: Tax morale, MSMEs